TECHNOLOGY AND ARTS SCIENCE FOR SOCIETY (IbM) THE MANAGEMENT OF JIPANGAN TOURISM VILLAGE - Yohana Ari Ratnaningtyas (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Ability and skill of the administrator in managing the Jipangan touristy village were deemed very limited,therefore a workshop in enhancing the quality is needed. Thus, the expected target is the enhancement ofthe ability and the knowledge of the administrator in Jipangan touristy village in the field of managementand tourism. The methods employed were program socialization to promote communication and to helpincrease the understanding of the administrators about the importance of developing the ability in managinga touristy village. Together with the team, they identified and studied the problem, the potencies, andchances which then arranged in a plan and implemented as workshops aiming to improve the ability of theparticipants in comprehending the issues of management and tourism in enhancing the touristy village andto give practical experience in accordance with the latest development. The materials given wereManagement Workshop, Performing Arts and Tourism Workshop. Monitoring and evaluation wereconducted to monitor all workshops, both the process of implementation and the expected results so theycould be well elaborated as stated in the initial objective. The result showed that the administrators got anew perspective and knowledge about how to run a touristy village well so it could develop. In the end ofthe workshop some donations were handed over, such as costumes for jathilan, brochures, and companyprofile witnessed by the administrators, representatives from Tourism Office Bantul, and local residents.